Thioredoxin Reductase-Type Ferredoxin: NADP+ Oxidoreductase of Rhodopseudomonas palustris: Potentiometric Characteristics and Reactions with Nonphysiological Oxidants - Mindaugas Lesanavičius; Daisuke Seo; Narimantas Čėnas (Antioxidants, 2022)
Rhodopseudomonas palustris ferredoxin:NADP+ oxidoreductase (RpFNR) belongs to a novel group of thioredoxin reductase-type FNRs with partly characterized redox properties. Based on the reactions of RpFNR with the 3-acetylpyridine adenine dinucleotide phosphate redox couple, we estimated the two-electron reduction midpoint potential of the FAD cofactor to be −0.285 V. 5-Deaza-FMN-sensitized photoreduction revealed −0.017 V separation of the redox potentials between the first and second electron transfer events. We examined the mechanism of oxidation of RpFNR by several different groups of nonphysiological electron acceptors. The kcat/Km values of quinones and aromatic N-oxides toward RpFNR increase with their single-electron reduction midpoint potential. The lower reactivity, mirroring their lower electron self-exchange rate, is also seen to have a similar trend for nitroaromatic compounds. A mixed single- and two-electron reduction was characteristic of quinones, with single-electron reduction accounting for 54% of the electron flux, whereas nitroaromatics were reduced exclusively via single-electron reduction. It is highly possible that the FADH· to FAD oxidation reaction is the rate-limiting step during the reoxidation of reduced FAD. The calculated electron transfer distances in the reaction with quinones and nitroaromatics were close to those of Anabaena and Plasmodium falciparum FNRs, thus demonstrating their similar “intrinsic” reactivity.